Lost and found: Alopecosa krynickii (Araneae: Lycosidae) in the Crimea - Nadolny, Anton A. (Zootaxa, 2018)
The wolf spider genus Alopecosa Simon, 1885 contains 152 species (WSC 2017), 30 of which are poorly described. Alopecosa krynickii (Thorell, 1875) is one of the least known European species of wolf spiders, of which the single male was collected in November, 1860 (Logunov 2013a: fig. 3). The original description of the species was made by Thorell (1875a, b), without illustrations. Since then no studies on A. krynickii based on new material have been published. Recently, Logunov (2013a) redescribed this species on the basis of its holotype. This redescription allowed me to identify A. krynickii from newly collected material from the Crimea. The aim of the present paper is to redescribe the rare species Alopecosa krynickii, based on both sexes and to describe the female for the first time.